VARIABILITY AMONG DIFFERENT ISOLATES OF Sclerotium rolfsii Sacc. ASSOCIATED WITH STEM ROT DISEASE OF GROUNDNUT - K. SUPRIYA; HARI KISHAN SUDINI, J. VAMSHI, G. UMA DEVI, T. UMA MAHESWARI (The Journal of Research, PJTSAU, 2023)
Groundnut (Arachis hypogea L.) the king of oilseeds remains as the valuable source of all nutrients. Stem rot caused by Sclerotium rolfsii is a destructive disease responsible for serious yield losses in groundnut around the world. Variation in morphological and cultural characteristics of thirty isolates of Sclerotium rolfsii were studied based on their growth rate, colony type, growth type, sclerotial pattern, sclerotial type, scleroial color and sclerotial size using potato dextrose agar (PDA). Significant variability with reference to mycelial and sclerotial characters across isolates of S. rolfsii, collected from Warangal, Wanaparthy and Nagarkurnool districts of Telanagna was observed. The growth rate ranged from 0.76 to 1.35 mm/hr. All the isolates produced sclerotia on PDA medium. Most of the isolates produced the colonies which were raised at ends (n=14) followed by flat type (n=12) and raised type (n=4). As per mycelial growth type, most of the isolates were found highly profuse in growth (n=18) and few were profuse in growth (n=12). Likewise, the isolates exhibited considerable variation with respect to morphological characteristics. Wide variation was also found with respect to number of sclerotia per plate (58 to 536), pattern of sclerotia produced in Petri dish (scattered category (n=23) and peripheral (n=7)), colour of sclerotia (brown colour (n=13) followed by dark brown (n=9) and light brown (n=7)), size of sclerotia (0.17 mm to 2.34 mm). Principal Component Analysis extracted four main components, growth rate, colony type, growth type and sclerotial pattern, from the population that described the variability in the population most appropriately.